Breakfast practices and factors associated with skipping of breakfast in medical students - Saleemullah Abro , Quratulain Saleem , Jahanzaib Lashari,Gulnaz Khalid, Maham Khan,Fatima Malik , Saleemullah Abro , Quratulain Saleem , Jahanzaib Lashari,Gulnaz Khalid, Maham Khan,Fatima Malik (Journal of Rawalpindi Medical College, 2021)
Objectives: To find out the breakfast practices and factors associated with skipping breakfast in medical students of Karachi. Material and Methods: This is is a Descriptive cross-sectional study, conducted in public sector medical institutes of Karachi from 1st January to 31st March 2019. 382 medical students were enrolled after taking informed consent. Data were collected from included students of this study, who had an age of 18 to 24 years, and all other students having a history of lactose intolerance, anorexia nervosa, and food allergies were excluded from the study. Breakfast outcome (practices and skip or omit of breakfast) data were collected by self-made structured questionnaire and anthropometric data (height, weight) were recorded. Body mass index was calculated as weight (Kg)/height (m)2. Collected data were analyzed by using the Statistical Package for social sciences version 22. Results: The mean age and mean Body mass index of students were 20.83±1.54 and 15.53±3.5 respectively. The study outcomes on breakfast practices, among participants, showed 81.4% were taken breakfast, breakfast skippers were 18.6%, gender-based comparison between breakfast-skippers males (14.1%): females (85.9%) were respectively and shortage of time is the main factor (56.3%) associated with breakfast skipping in students. There is no significant (p>0.05) association between Gender-based comparison between factors associated with breakfast skipping. Conclusion: The breakfast skippers were 18.6%, and among the main factors associated with skipping of breakfast was a shortage of time (56.3%).